3D printed models vs conventional models : comparison of aerodynamic performance for wind tunnel experiments - Haziq Idraki Shahidin,; Mohd Rosdzimin Abdul Rahman,; Azam Che Idris,; Mohd Rashdan Saad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Traditionally, wind tunnel models are made of metal and the processes are very expensive. Since then, many researchers have been looking for new alternatives, hence 3D printing technology is the solution. Under right test conditions, 3D printed parts could be tested in a wind tunnel to get the aerodynamic performances. By using 3D printing technology, the cost and time can be significantly reduced to produce the wind tunnel models. This investigation was done to compare the aerodynamic performances which are drag and lift forces of the existing wind tunnel metal models with 3D printed wind tunnel models. Polylactic acid (PLA) was used as the printing materials by using two 3D printers which are Poseidon X and CR-10 S5. The wind tunnel testing covered the wind speed in the range of 0.57 m/s to 10.35 m/s at angleof- attack of 0°. Results from experiments show that the drag and lift forces of the 3D printed models show very close similarities with the metal models. It can be concluded that the wind tunnel models produced by using 3D printing technology can be used in wind tunnels for early testing.